2014
DOI: 10.1111/jdv.12715
|View full text |Cite
|
Sign up to set email alerts
|

Infectious eczematoid dermatitis: a comprehensive review

Abstract: Infectious eczematoid dermatitis (IED) is characterized by an acute eczematous eruption triggered by purulent discharge from a primary infected site. Alcohol consumption, cigarette smoking and occupations with higher incidences of contact dermatitis portend increased risk for IED. Staphylococcus aureus is the most commonly cultured microbe from affected skin, with Streptococcus species the second most. Patients are first evident with peripherally spreading vesicles and pustules radiating from an infected site.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
(44 reference statements)
0
13
0
2
Order By: Relevance
“…This condition is defined as an acute, eczematous eruption that occurs secondary to autosensitization to purulent drainage from a primary infected site. 7 In a 1902 study of 1200 new patients to an outpatient dermatology clinic, Engman reported that 35, or 2.9%, had presentations consistent with IED. 8 A study at the Mayo Clinic examining inpatient dermatology admissions from 2000-2010 reported similar results, finding that 2.9% of 2216 admissions were due to IED.…”
Section: Case Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…This condition is defined as an acute, eczematous eruption that occurs secondary to autosensitization to purulent drainage from a primary infected site. 7 In a 1902 study of 1200 new patients to an outpatient dermatology clinic, Engman reported that 35, or 2.9%, had presentations consistent with IED. 8 A study at the Mayo Clinic examining inpatient dermatology admissions from 2000-2010 reported similar results, finding that 2.9% of 2216 admissions were due to IED.…”
Section: Case Presentationmentioning
confidence: 99%
“…9 IED is believed to develop when purulent drainage from a primary infection causes autosensitization, with hypersensitivity developing as bacterial products act as haptens and stimulate an immune response. 7 Staphylococcal and/or Streptococcal species are most commonly associated with IED. 10 In this case, interdigital tinea pedis, and associated bacterial infection, flourished in the warm, moist environment of the patient's wet boots over two days.…”
Section: Case Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Микробная экзема представляет собой экзематозный процесс, обусловленный сенсибилизацией кожи к антигенам пиококковой флоры и дрожжевых грибов [13]. Основным клиническим проявлением дерматоза является возникновение островоспалительных везикулезных высыпаний в ответ на антигенную стимуляцию из инфекционного очага [14]. Первый синоним болезни был придуман Engman в 1902 году, который назвал патологию «стафилогенный экзематоидный дерматит» [15].…”
Section: микробная экземаunclassified